Analysis of artificial opals by scanning near field optical microscopy - Barrio, J. (2011)
Herein we present a detailed analysis of the optical response of artificial opal films realized employing a near-field scanning optical microscope in collection and transmission modes. Near-field patterns measured at the rear surface when a plane wave impinges on the front face are presented with the finding that optical intensity maps present a clear correlation with the periodic arrangement of the outer surface. Calculations based on the vector Korringa-Kohn-Rostoker method reproduce the different profiles experimentally observed as well as the response to the polarization of the incident field. These observations constitute the first experimental confirmation of the collective lattice resonances that give rise to the optical response of these three dimensional periodic structures in the high-energy range. © 2011 American Institute of Physics.